Assimilation Theory, Attention, and Asymmetry in Müller-Lyer Illusions: Quantitative Predictions. Issue 2 (October 2014) - Pressey, Alexander W.
The manner in which Pressey's assimilation theory of geometric illusions (e.g., Pressey & Pressey, 1992) operates is illustrated by considering the basic question of why shrinkage and expansion forms of Müller-Lyer's illusions differ. The traditional answer is that the differences are due to the fact that the two forms generate "fundamentally different" kinds of illusions. Three experiments, each purporting to support this view, were simulated by the quantitative version of the theory. Because the theory correctly predicted complex means and variances, it was concluded that the traditional position was not valid.